Online social participation among older malaysian living with dementia during the pandemic COVID-19: the ‘take the purple pledge’ project - Sumaiyah Mat,; Chua, Qi Qi; Vigneswaran Krishna,; Akmaliza Ali,; Susheel Kaur Dhillon Joginder Singh,; Farahiyah Wan Yunus, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The ‘Take the Purple Pledge’ project a collaborative project between UKM and the Alzheimer’s Disease Foundation Malaysia (ADFM) was conducted. The undergraduate students from the Speech Sciences, Physiotherapy, Occupational Therapy, and Audiology programs organized this event as part of the Community Based Rehabilitation course requirement. The program’s main objective was to engage with individuals with dementia and their caregivers. The ‘Take the Purple Pledge’ project consisted of two parts: (i) an interactive session with individuals with dementia and (ii) posting posters and materials on social media to spread awareness about dementia among the public. The first part of the program was conducted via Zoom on 14th August 2021 from 8:00 am to 11:30 am, while the second part of the program was completed on the same date. For the interactive session, 99 participants comprising students, ADFM staff, individuals living with dementia, and their caregivers attended the Zoom session, filled with virtual activities such as exercises, memory games, gamebooks, checklists, and tours. Individuals with dementia, their caregivers and staff from ADFM provided positive feedback about the program. The ‘Take the Purple Pledge’ program not only allowed individuals with dementia and their caregivers to interact with other people, it also provided an opportunity for them to participate and be included in a social event during this challenging time.